Centelhas de uma cidade turística nos cartões-postais de Jaeci Galvão (1940-1980) - Silva, Sylvana Kelly Marques da (2012)
The postcard is a medium that has gained popularity at the time that the picture was linked to its support. It circulated favoring mainly the views of the cities and composed a triad between landscape, photography and tourism. The visuality that loads is among signs of representations, relationships, forms of collective consciousness and ways of seeing the world. In Natal, the photographer Jaeci Emereciano Galvão registered urban and social transformations focusing on interventions that emphasized urban centres as social space and progress and nature as a space for contemplation and enjoyment. They are images with social and cultural issues very clear, since the picture is from a process of creation that is all about choices and decisions about what deserves to be photographed. Therefore, the aim of this research by investigating the role of photographs evidenced in Jaeci’s postcards, with a view to inclusion of tourism in the spaces of Natal and the visuality assumed in the context of their own identity. The theoretical framework that makes up the discussions about the landscape, the city's tourism and photographic representation in postcards emerged from the literature of Schama (1996), Corbin (1989), Cosgrove (1998), Benjamin (1987), Kossoy (2003; 2006; 2009) and Souza Martins (2009), which gave grants to interpret and understand the symbolic construction presented in the postcards. Methodologically the work was done through research in archives, newspapers, postcards of the survey, interviews, iconographic and iconological analyses proposed by Kossoy. At the end, it was concluded the Jaeci Galvão’s postcards established themselves as essential elements for symbolic landscapes of tourism in Natal.